Cadmium is acutely toxic for murine hepatocytes, effects on intracellular free Ca2+ homeostasis - Wang, S. S; Chen, L; Xia, S. K (Physiological research, 2007)
We studied cadmium toxicity in murine hepatocytes in vitro. Cadmium effects on intracellular free Ca2+ concentration ([Ca2+]i) were assayed, using a laser scanning confocal microscope with a fluorescent probe, Fluo-3/AM. The results showed that administration of cadmium chloride (CdCl2, 5, 10, 25 µM) resulted in a dose-dependent decrease of hepatocyte viability and an elevated aspartate aminotransferase (AST) activity in the culture medium (p<0.05 for 25 µM CdCl2 vs. control). Significant increases of lactate dehydrogenase (LDH) activities in 10 and 25 µM CdC12-exposed groups were observed (p<0.05 and p<0.01, respectively). A greatly decreased albumin content and a more malondialdehyde (MDA) formation also occurred after CdC12 treatment. The Ca2+ concentrations in the culture medium of CdCl2-exposed hepatocytes were significantly decreased, while [Ca2+]i appeared to be significantly elevated (p<0.05 or p<0.01 vs. control). We found that in Ca2+-containing hydroxyethyl piperazine ethanesulfonic acid-buffered salt solution (HBSS) only, CdCl2 elicited [Ca2+]i increases, which comprised an initially slow ascent and a strong elevated phase. However, in Ca2+-containing HBSS with addition of 2-aminoethoxydiphenyl borane (2-APB), CdCl2 caused a mild [Ca2+]i elevation in the absence of an initial rise phase. Removal of extracellular Ca2+ showed that CdCl2 induced an initially slow [Ca2+]i rise alone without being followed by a markedly elevated phase, but in a Ca2+-free HBSS with addition of 2-APB, CdCl2 failed to elicit the [Ca2+]i elevation. These results suggest that abnormal Ca2+ homeostasis due to cadmium may be an important mechanism of the development of the toxic effect in murine hepatocytes. [Ca2+]i elevation in acutely cadmium-exposed hepatocytes is closely related to the extracellular Ca2+ entry and an excessive release of Ca2+ from intracellular stores.
Keywords: hepatocyty; finanční podpora výzkumu jako téma; Hepatocytes; Animals; homeostáza; myši inbrední ICR; chlorid kademnatý; poruchy metabolismu vápníku; Research Support as Topic; zvířata; Microscopy, Confocal; konfokální mikroskopie; Homeostasis; Cadmium Chloride; kadmium; Calcium Metabolism Disorders; Mice, Inbred ICR; Cadmium